Pemanfaatan Teknologi ColdFusion Dalam Pembuatan Web Deteksi Gejala Awal Penyakit - Azinar, Azmuri Wahyu (INTEGER: Journal of Information Technology, 2023)
Abstract. The shortage of doctors in Indonesia has forced some people to self-diagnose, especially for minor ailments, such as coughs, colds, or diarrhea, which usually do not require a special examination by an expert or complex treatment and these disorders usually heal on their own, even without treatment. But ordinary people may not suspect that symptoms such as dizziness or ordinary coughing can also be an indication of a more serious illness. What emergency measures should be taken first in urgent conditions, including when you have an accident or injury at home, we need to know and master from an accountable source. The internet is now able to answer the need for information needed in various sectors of life, including the health sector. Making a dynamic and interactive website can be an alternative for people to find that information. Coldfusion technology enables developers to easily build and deploy dynamic websites, content creation systems, commerce applications and so on. The website for detecting symptoms of this disease uses several charts that must be answered by the user. The charts contained on this web will guide the user through a series of questions about the symptoms experienced by the user to suggest possible causes and the most appropriate course of action. From the results of the answers given, it will be diagnosed whether the user can safely self-medicate the symptoms or whether it requires medical attention. The convenience of scripts in ColdFusion such as CFINSERT, CFQUERY, CFCOOKIE and many more, makes it easy to integrate with HTML tags. At the end of the process, a user acceptance test is carried out which aims to test the features in the system by prospective users with the aim of whether the system can be used.Keywords: ColdFusion, Diagnose, symptom  Abstrak. Kekurangan jumlah dokter di Indonesia membuat beberapa orang melakukan diagnosa sendiri khususnya untuk penyakit ringan, seperti batuk, pilek atau diare yang biasanya tidak memerlukan pemeriksaan khusus seorang ahli atau pengobatan yang rumit dan gangguan tersebut biasanya akan sembuh sendiri, bahkan tanpa diobati sekalipun. Tetapi bagi orang awam mungkin tidak menduga bahwa gejala seperti pusing atau batuk-batuk biasa, bisa juga merupakan petunjuk adanya penyakit yang lebih serius. Tindakan darurat apa yang harus dilakukan pertama kali saat kondisi mendesak, termasuk saat mengalami kecelakaan atau cedera di dalam rumah, perlu kita ketahui dan kuasai dari sumber yang dapat dipertanggungjawabkan. Internet saat ini sudah dapat menjawab kebutuhan informasi yang dibutuhkan di berbagai sektor kehidupan termasuk bidang kesehatan. Pembuatan website yang dinamis dan interaktif bisa menjadi alternatif bagi orang untuk mencari informasi tersebut. Teknologi Coldfusion memungkinkan pengembang untuk dengan mudah membangun dan menggunakan situs web dinamis, sistem pembuatan konten, aplikasi commerce dan sebagainya. Website deteksi gejala penyakit ini  menggunakan beberapa bagan yang harus dijawab oleh pengguna. Bagan-bagan yang terdapat di dalam web ini akan memandu pengguna melalui serangkaian pertanyaan tentang gejala yang dialami oleh pengguna untuk menyarankan kemungkinan penyebab dan tindakan yang paling tepat. Dari hasil jawaban yang diberikan, akan diagnosa apakah penguna dapat mengobati sendiri gejalanya dengan aman atau apakah memerlukan perhatian medis. Kemudahan script dalam ColdFusion seperti CFINSERT, CFQUERY, CFCOOKIE dan masih banyak lagi, memberikan kemudahan dalam melakukan integrasi dengan tag HTML Pada akhir proses, dilakukan user acceptance test yang bertujuan melakukanpengujian terhadap fitur-fitur yang ada pada sistem oleh calon pengguna dengan tujuan apakah sistem  benar-benar bisa digunakan.Kata Kunci: ColdFusion, Diagnosa, Gejala